VIA-7 Method: A seven perceptual parameters methodology for the assessment of visual impact caused by wind and solar facilities on the landscape in cultural heritage sites. (September 2022) - Diego, Jesús C.; Bonete, Saray; Chías, Pilar
Abstract: Renewable energy facilities have given rise to several conflicts due to their visual impact on the environment. This is due, among others, to their proliferation, extension, and placement, often in highly visible locations. Previous methodologies used to assess the visual impact of these facilities on the landscape do not generally consider such important aspects as cultural heritage or local values. This article gives a full description of the " VIA-7 Method ", a novel methodology with a cultural emphasis, permitting the assessment of the visual impact caused by wind and solar facilities on the landscape in the vicinity of cultural heritage sites by considering seven perceptual parameters: total cultural importance of the heritage site, facility magnitude, visual incidence, total contrast, accessibility, qualitative distance and public opinion. The application of the VIA-7 Method needs of several steps to include important values of local cultural heritage into the assessment process: delimitation of the area of study and the Area of Visual Influence, preparation of the required cartographical data, analysis of the convergent visibility of the area of study, analysis of the visual quality and visual fragility of each Zone of Potential Concentration of Observers in order to calculate the partial visual impact for each one of them, weighting each partial visual impact by the survey results and a final calculation of the total visual impact. Implementation of the VIA-7 Method brings public administrations new possibilities for decisions concerning wind and solar facilities near cultural heritage sites which would be protective with the landscape. Highlights: Renewable energy facilities have an impact on cultural heritage sites. Current visual impact assessment methodologies do not consider cultural aspects. The VIA-7 Method is a methodology based on seven perceptual and cultural parameters, both qualitative and quantitative. The VIA-7 Method includes public opinion among factor analysis for visual impact assessment of wind and solar facilities. The VIA-7 Method allows to protect, manage, and regulate territories in accordance with the European Landscape Convention.